Evaluating the elimination of iCasp9-IL15 CAR-T cells using photosensitizers AP20187 in vitro - Mao, Can Van; Cuong, Le Duy (Tạp chí Nghiên cứu Y học, 2025)
This study was conducted to evaluate the ability to eliminate iCasp9-IL15 Chimeric Antigen Receptor-T (CAR-T) cells using the photosensitizers AP20187 in vitro. Peripheral blood mononuclear cells (PBMC) were activated with Dynabeads Human T-Activator CD3/CD28 and IL-2 to optimize the concentration of the antibiotic blasticidin for screening iCasp9-IL15 CAR-T cells. iCasp9-IL15 CAR-T cells after proliferation with 1D2 artificial antigen-presenting cells, were screened using blasticidin. Subsequently, the iCasp9 suicide gene of these cells was activated at various concentrations of AP20187 photosensitizer. The results showed that after 5 days of culture, a blasticidin concentration of 15.0 µg/mL was used to screen iCasp9-IL15 CAR-T cells (activated, non-transformed PBMC showed > 95% cell death). The proportion of iCasp9-IL15 cells after blasticidin screening reached approximately 75%. Using AP20187 at the concentration of 20 nM resulted in almost complete elimination of iCasp9-IL15 CAR-T cells (survival rate: 2.14%). So, iCasp9-IL15 CAR-T cells can almost be eliminated by AP20187 at a concentration of 20 nM in case of high toxicity during treatment.